2021
DOI: 10.1245/s10434-021-10847-9
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Breast Biopsy After Neoadjuvant Systemic Treatment for Reliable Exclusion of Residual Cancer in Breast Cancer Patients

Abstract: Background About 40 % of women with breast cancer achieve a pathologic complete response in the breast after neoadjuvant systemic treatment (NST). To identify these women, vacuum-assisted biopsy (VAB) was evaluated to facilitate risk-adaptive surgery. In confirmatory trials, the rates of missed residual cancer [false-negative rates (FNRs)] were unacceptably high (> 10%). This analysis aimed to improve the ability of VAB to exclude residual cancer in the breast reliably by identifying key chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 21 The low sensitivity (high rate of missed residual cancer) of VAB alone is in line with our previous research, which showed that for the reliable exclusion of residual cancer, VAB should be combined with imaging and specific patient selection criteria. 9 , 22 Recent studies showed that an ‘intelligent VAB’, a machine learning algorithm analyzing VAB variables alongside clinical and patient information, can reliably exclude residual cancer after NAST; these patients without residual disease might be spared breast and axillary surgery. 10 , 23 Thus, future trials may evaluate oncologic outcomes of response assessment to NAST via VAB within three patient groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 21 The low sensitivity (high rate of missed residual cancer) of VAB alone is in line with our previous research, which showed that for the reliable exclusion of residual cancer, VAB should be combined with imaging and specific patient selection criteria. 9 , 22 Recent studies showed that an ‘intelligent VAB’, a machine learning algorithm analyzing VAB variables alongside clinical and patient information, can reliably exclude residual cancer after NAST; these patients without residual disease might be spared breast and axillary surgery. 10 , 23 Thus, future trials may evaluate oncologic outcomes of response assessment to NAST via VAB within three patient groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…False-negative rates (FNR, rate of missed cancer in the biopsy compared to the surgical specimen) were higher than anticipated with 18–50% [ [31] , [32] , [33] , [34] ]. Subgroup analyses showed that the biopsies mainly miss small, heterogenous responding tumor foci and suggested lower FNRs when specific patient selection criteria were applied (tumor size after NAST <2 cm, at least six biopsy samples, biopsy sample representative of tumor bed, and triple-negative or HER2+ breast cancer) [ 31 , 32 , 35 ]. Based on these results, a multi-modal machine learning algorithm using patient, tumor, imaging, and biopsy variables (“intelligent vacuum-assisted biopsy (VAB)”) was developed.…”
Section: Conventional and Ai-based Response Assessment To Neoadjuvant...mentioning
confidence: 99%
“…On recent further analysis of the same data, age and presence of DCIS were found to be associated with the FNR. In a selected sub-cohort of patients with unicentric disease, not associated with DCIS and a representative VAB, the FNR was 2.9% [ 23 ].…”
Section: De-escalation Of Breast Surgerymentioning
confidence: 99%